PENGARUH MODEL PEMBELAJARAN JIGSAW TERHADAP KEMAMPUAN KOMUNIKASI LISAN DAN HASIL BELAJAR SISWA - Mila Vanalita; Tri Jalmo; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2014)
This research was aimed at determining the effect of Jigsaw learning model to students' verbal communication skills and learning outcomes which the design was pretest posttest for non equivalent groups. The samples were students of class VII A and VII B which were selected by purposive sampling. The qualitative data such as the average score of students' oral communication skills and students' responses questionnaire were analyzed descriptively. The quantitative data were obtained from the average score of pretest, posttest, and gain then statistically analyzed using t-test and U test. The results showed that the students of experimental class had an average score of verbal communication skills with good criterion (81.48). Students’ learning outcomes had increased, with an average gain (0.57). Most of the students (96.30%) gave  positive responses to the implementation of Jigsaw cooperative learning. Thus, Jigsaw cooperative learning model was influential in improving students’ oral communication skills and learning outcomes. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran tipe Jigsaw terhadap kemampuan komunikasi lisan dan hasil belajar siswa dengan desain pretes-postes kelompok tak  ekuivalen. Sampel penelitian adalah siswa kelas VII A dan VII B yang dipilih secara purposive sampling. Data kualitatif berupa rata-rata nilai kemampuan komunikasi lisan siswa dan angket tanggapan siswa yang dianalisis secara deskriptif. Data kuantitatif diperoleh dari rata-rata nilai pretes, postes dan gain, kemudian dianalisis secara statistik menggunakan uji-t dan uji U. Hasil penelitian menunjukkan rata-rata siswa kelas eksperimen memiliki kemampuan komunikasi lisan dengan kriteria baik (81,48). Hasil belajar siswa mengalami peningkatan, dengan rata-rata gain (0,57).  Sebagian besar siswa (96,30 %) memberikan tanggapan positif terhadap penerapan model pembelajaran kooperatif tipe Jigsaw. Dengan demikian, model pembelajaran kooperatif tipe Jigsaw berpengaruh dalam meningkatkan kemampuan komunikasi lisan dan hasil belajar siswa. Kata kunci : hasil belajar, komunikasi lisan, pembelajaran kooperatif Jigsaw